Pitfall of Thyroid Storm Score - Rakhman, Muhammad; Rosandi, Rulli (Clinical and Research Journal in Internal Medicine, 2023)
The thyroid storm is an emergency characterized by multiple organ failure due to severe thyrotoxicosis that is often triggered by other diseases. The diagnosis of thyroid storm is made clinically in a severe thyrotoxic patient with evidence of systemic decompensation. The Burch–Wartofsky Point Scale (BWPS) is a score that is widely used to diagnose thyroid storm, introduced by Burch and Wartofsky in 1993. In Burch–Wartofsky Point Scale, the thyroid storm diagnosis is made if there is clinically severe thyrotoxicosis with a score of 45 in a patient that has a previous history of elevated free fT3  (triiodothyronine) or fT4 (free thyroxine). But in a condition it cannot be distinguished whether a condition is caused by the effects of thyrotoxicosis or due to other diseases, then these symptoms are considered as a result of the effects of thyrotoxicosis. In the Burch–Wartofsky Point Scale, there is a pitfall. If we are accustomed to assuming a worsening of the condition in thyroid patients as a result of the effects of thyrotoxicosis, without trying to exclude the condition due to other conditions can lead to a misdiagnosis of thyroid storm. This article aims to remind us to be careful in applying diagnostic tools in diagnosing a thyroid storm.